The Role of Thiamine Pyrophosphate in Prevention of Cisplatin Ototoxicity in an Animal Model - Ozan Kuduban; Cuneyt Kucur; Ebru Sener; Halis Suleyman; Fatih Akcay (The Scientific World Journal)
Objective. The aim of this study was to evaluate the effectiveness of thiamine pyrophosphate against cisplatin-induced ototoxicity in guinea pigs. Materials and Methods. Healthy guinea pigs (n=18) were randomly divided into three groups. Group 1 (n=6) received an intraperitoneal injection of saline solution and cisplatin for 7 days, group 2 (n=6) received an intraperitoneal injection of thiamine pyrophosphate and cisplatin for 7 days, and group 3 (n=6) received only intraperitoneal injection of saline for 7 days. The animals in all groups were sacrificed under anesthesia, and their cochleas were harvested for morphological and biochemical observations. Results. In group 1, receiving only cisplatin, cochlear glutathione concentrations, superoxide dismutase, and glutathione peroxidase activities significantly decreased (P<0.05) and malondialdehyde concentrations significantly increased (P<0.05) compared to the control group. In group 2, receiving thiamine pyrophosphate and cisplatin, the concentrations of enzymes were near those of the control group. Microscopic examination showed that outer hair cells, spiral ganglion cells, and stria vascularis were preserved in group 2. Conclusion. Systemic administration of thiamine pyrophosphate yielded statistically significant protection to the cochlea of guinea pigs from cisplatin toxicity. Further experimental animal studies are essential to determine the appropriate indications of thiamine pyrophosphate before clinical use.